2021
DOI: 10.1161/hypertensionaha.121.17396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Lifestyle and Diet on Perinatal DNA Methylation Signatures Associated With Childhood Arterial Stiffness at 8 to 9 Years

Abstract: Increases in aortic pulse wave velocity, a measure of arterial stiffness, can lead to elevated systolic blood pressure and increased cardiac afterload in adulthood. These changes are detectable in childhood and potentially originate in utero, where an adverse early life environment can alter DNA methylation patterns detectable at birth. Here, analysis of epigenome-wide methylation patterns using umbilical cord blood DNA from 470 participants in the Southampton’s Women’s Survey identified differential methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Although the exact mechanism remains unknown, the earliest signs of CVD could originate already in the developing fetus, possibly mediated through epigenetic mechanisms [ 21 ]. Murray et al reported that maternal risk factors during pregnancy could induce DNA methylation in the offspring’s genome at birth, which in turn, was found to be associated with enhanced arterial stiffening after a follow-up of 8–9 years [ 22 ]. In addition, offspring of mothers with pregestational diabetes have been observed to have an increased risk for pathological ventricular hypertrophy already at birth [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism remains unknown, the earliest signs of CVD could originate already in the developing fetus, possibly mediated through epigenetic mechanisms [ 21 ]. Murray et al reported that maternal risk factors during pregnancy could induce DNA methylation in the offspring’s genome at birth, which in turn, was found to be associated with enhanced arterial stiffening after a follow-up of 8–9 years [ 22 ]. In addition, offspring of mothers with pregestational diabetes have been observed to have an increased risk for pathological ventricular hypertrophy already at birth [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CpG methylation of these regions in cardiac myocytes inversely correlates with gene expression. 9 As mentioned, Murray et al 3 them aortic pulse wave velocity by magnetic resonance imaging and correlated with CpG methylation. Essentially, 16 CpG loci were identified to be associated with aortic pulse wave velocity, with 8 being associated with prenatal modifiable risk factors of the mother.…”
Section: See Related Article Pp 787-800mentioning
confidence: 99%
“…The different epigenetic layers include DNA and histone modifications as well as spatial genome organization and noncoding RNAs. For practical reasons, epigenome-wide association studies, like the one presented by Murray et al, 3 largely focused on DNA methylation, or more precisely on methylation of the cytosine-phosphate-guanine palindrome (CpG). 6 Most methods to detect DNA methylation rely on the conversion of unmethylated cytosine to thymine.…”
Section: See Related Article Pp 787-800mentioning
confidence: 99%
“…Among these, 13 out of 15 suggestive DMRs were positively associated with AIx. The association results of suggestive DMRs and their inclusive CpGs for six AS/PH traits are presented in Supplementary Tables [13][14][15][16][17][18]. Overall, the number of CpGs included in suggestive DMRs ranged from 3 to 7.…”
Section: Ewas At Co-methylated Genomic Regionsmentioning
confidence: 99%